2023
DOI: 10.3389/fmars.2023.1200788
|View full text |Cite
|
Sign up to set email alerts
|

Stratigraphic evolution and drowning steps of a submerged isolated carbonate platform in the northern South China Sea

Abstract: Drowned carbonate platforms on passive margins present a paradox, because their great growth potential exceeds the typical rates of passive margin subsidence and any relative sea-level rise driven by long-term processes in the geologic record. In this study, manned submersible observations, sampling, and high-resolution acoustic data were used to investigate a drowned isolated carbonate platform cropping out at a water depth of 536–800 m in the northern South China Sea. Based on the results, the Early Miocene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…The Qiongdongnan Basin is a NE-trending Cenozoic petroliferous basin located in the northwestern South China Sea (Figure 1). It is bounded by Hainan Island to the north, Yinggehai-Song Hong Basin to the west, Xiasha Uplift to the south, and Pearl River Mouth Basin to the east, and covers a region of ~8×10 4 km 2 (Chen et al, 2023) (Figures 1, 2). Currently, the water depth ranges from 300 m to 2750 m with a margin of continental shelf developed (Figure 2).…”
Section: Geological Settingmentioning
confidence: 99%
“…The Qiongdongnan Basin is a NE-trending Cenozoic petroliferous basin located in the northwestern South China Sea (Figure 1). It is bounded by Hainan Island to the north, Yinggehai-Song Hong Basin to the west, Xiasha Uplift to the south, and Pearl River Mouth Basin to the east, and covers a region of ~8×10 4 km 2 (Chen et al, 2023) (Figures 1, 2). Currently, the water depth ranges from 300 m to 2750 m with a margin of continental shelf developed (Figure 2).…”
Section: Geological Settingmentioning
confidence: 99%
“…It is a typical drowned, isolated carbonate platform. New evidence from a foraminifer and stratigraphic correlation showed that it was drowned during the middle of the Miocene [16].…”
Section: Geological Backgroundmentioning
confidence: 99%
“…A recent study showed that the Ganquan platform was drowned during the middle Miocene [16] when most other Xisha carbonate platforms were in a flourishing stage (middle Miocene) and were later drowned in the late Miocene [15,27]. Hence, there is little chance that the Ganquan platform experienced a subaerial environment with fresh meteoric dissolution.…”
Section: Origins Of the Submarine Sinkholes In The Ganquan Platformmentioning
confidence: 99%
See 1 more Smart Citation